1998
DOI: 10.1007/s002239900430
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fracture History and Prospective Bone Fracture Risk of Hemodialysis Patients are Related to Apolipoprotein E Genotype

Abstract: This investigation of 219 hemodialysis patients relates the history and prospective risk of bone fractures to apolipoprotein E (apoE) genotype. A greater percentage of the 41 patients with the E3/4 and E4/4 genotypes than of the 38 patients with the E2/3 and E2/2 genotypes had a history of bone fractures at the time of recruitment (44% versus 16%, P < 0.005). During the 4 years following recruitment, more of the patients with apoE genotypes E3/4 and E4/4 than with apoE genotypes E2/3 and E2/2 suffered bone fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 18 publications
3
58
6
Order By: Relevance
“…In our study, there were no associations between apoE genotype and plasma phylloquinone, in contrast to that previously described in hemodialysis patients (Saupe et al, 1993;Kohlmeier et al, 1998). This difference may be due to several factors including the greater range and lower intrasubject variance of plasma phylloquinone in these patients, their more controlled diet and presence of hyperlipidaemia in some patients Kohlmeier et al, 1998).…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan contrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, there were no associations between apoE genotype and plasma phylloquinone, in contrast to that previously described in hemodialysis patients (Saupe et al, 1993;Kohlmeier et al, 1998). This difference may be due to several factors including the greater range and lower intrasubject variance of plasma phylloquinone in these patients, their more controlled diet and presence of hyperlipidaemia in some patients Kohlmeier et al, 1998).…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan contrasting
confidence: 99%
“…This difference may be due to several factors including the greater range and lower intrasubject variance of plasma phylloquinone in these patients, their more controlled diet and presence of hyperlipidaemia in some patients Kohlmeier et al, 1998). Our study does not demonstrate that the influence of apoE on osteocalcin g-carboxylation was mediated via its influence on plasma phylloquinone.…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan contrasting
confidence: 60%
See 2 more Smart Citations
“…(11,33) The evidence from our study that apoE has a role in osteoblast uptake of lipoprotein-borne vitamin K is consistent with recent evidence linking apoE polymorphism, vitamin K status, and bone health. (5-8,34 -40) An original report that apoE4 was associated with an increase in self-reported fractures in hemodialysis patients (39) has been confirmed in a prospective study in healthy, elderly white women (40) and a study in Japanese women showed that the apoE4 allele was associated with a reduced bone mineral density (BMD). (38) Our findings suggest the possibility that an enhanced uptake of TRL-vitamin K may be a general property of apoE4-secreting cells but that in vivo this results in an increased hepatic uptake, which has a sparing effect on the availability of vitamin K to bone.…”
Section: Newman Et Almentioning
confidence: 96%